KOMUNIKASI TERAPEUTIK PENYEHAT TRADISIONAL BALIAN USADA DI BALI - Ni Made Sinarsari; I Gede Sutana (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2023)
Communication is needed in various professions that are engaged in by humans, including the profession of health workers. Communication carried out by health workers is therapeutic communication which aims to build a relationship of trust between health workers and patients in the process of handling the patient's illness. Therapeutic communication is not only done by modern health workers such as midwives, nurses, and doctors. However, health workers such as Balian Usada in Bali also use therapeutic communication to facilitate the communication process in handling and healing patients' illnesses. This research is a study of the phenomenon of therapeutic communication which is not only carried out by modern health workers but also by traditional health workers. In the process of collecting data, this research uses the method of literature study and document analysis related to the field of study, and is presented by means of interpretation and description analysis. From this research it can be seen that Balian Usada is a Balinese traditional healer who learns medicine consciously, either through Guru Waktera learning from Balinese medicine experts, or self-taught through Lontar Usada. Balian Usada has a professional ethics of Balian or Sesana Balian. Sesananing Balian is a code of ethics that is mandatory as a moral control for usada in carrying out their profession. Balian Usada builds patient trust and comfort through anamnesis. When the patient feels trust and comfort and the communication has gone both ways, Balian Usada then plans the patient's treatment according to the patient's complaints. Good and effective communication has a significant impact on the patient's recovery. Poor communication can be a problem in patient care. Developing easy communication is essential to reduce patient anxiety.Â  Keywords: Therapeutic Communication; Traditional Healer; Balian Usada